Konzervativno ali kirurško zdravljenje otrok s prirojenimi nepravilnostmi sečil? - Novljan, Gregor (Slovenska pediatrija, 2023)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of end-stage renal failure in children. Timely diagnosis and appropriate treatment are crucial and usually involve the collaboration of different healthcare professionals. Managing the primary developmental disorder can be conservative, surgical, or combined. We must also consider and address the possible complications and any associated health issues of the child. Due to the broad subject matter, we decided to narrow our focus on the management and surgical treatment of those cases where the indication for surgical treatment is unclear. Since the treatment of children with obstructive nephropathy and lower urinary tract dysfunction is described in separate articles, we were left with presenting the treatment of children with multicystic dysplastic kidneys (i.e., dysplastic kidney) and children with congenital vesicoureteral reflux. Conservative management and surgical treatment methods are described, and we provide some recent insights into the indications for surgery. The optimal treatment of these children still needs to be clarified. An individual approach is crucial, and maintaining kidney function is the primary goal of therapy
Keywords: children; congenital anomalies of the kidney and urinary tract; multicistično displastična ledvica; multicystic dysplastic kidney; otroci; prirojene nepravilnosti sečil; treatment; vesicoureteral reflux; vezikoureteralni refluks; zdravljenje